The uranium isotopic record of shales and carbonates through geologic time. (1st May 2021) - Chen, X.; Tissot, F.L.H.; Jansen, M.F.; Bekker, A.; Liu, C.X.; Nie, N.X.; Halverson, G.P.; Veizer, J.; Dauphas, N.
Abstract: In the modern ocean, U reduction and incorporation into anoxic sediments imparts a large isotopic fractionation of approximately +0.6‰ that shifts the seawater δ 238 U value ( 238 U/ 235 U, expressed as δ 238 U per mil deviation relative to CRM-112a) relative to continental runoff. Given the long residence time of U in the modern oceans (∼400 kyr), the isotopic composition of carbonates (taken as a proxy for seawater) reflects the global balance between anoxic and other sinks. The U isotopic composition of open-marine carbonates has thus emerged as a proxy for reconstructing past changes in the redox state of the global ocean. A tenet of this approach is that the δ 238 U values of seawater and anoxic sediments should always be fractionated by the same amount. In order to test this hypothesis, we have measured the U concentrations and isotopic compositions of carbonates spanning ages from 3250 Ma to present. A first-order expectation for the Archean and possibly Proterozoic is that near-quantitative U removal to extensive anoxic sediments should have shifted the uranium isotopic composition of seawater and carbonates towards lower values. Instead, the measurements reveal that many Archean and Proterozoic carbonates have unfractionated δ 238 U values similar to those of continents and riverine runoff. These results are inconsistent with the view that the U isotopic composition of seawater simply reflects the areal extent of anoxic sediments in the past. We consider two plausible explanations for why the U isotopic composition of Archean and Proterozoic carbonates is not fractionated from the crustal and riverine composition: (1) the residence time of U could have been much shorter in the Precambrian oceans when anoxic settings were much more extensive, and (2) the process of incorporation of U into anoxic sediments in the Precambrian imparted a smaller U isotopic fractionation than in the modern because of differences in the efficiency or mechanism of uranium removal. This study highlights the challenges inherent to applying knowledge of the modern marine U isotopic cycle to periods of Earth's history when ocean-floor anoxia was much more extended, anoxic basins were ferruginous, and atmospheric oxygen content was significantly lower than present.